ANALISIS FAKTOR PENGARUH PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK KONTRUKSI GEDUNG REKTORAT DAN DEKANAT UNMAS DENPASAR - Tjokorda Istri Praganingrum; Ida Ayu Widi Adnyani (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2022)
Every construction project implementation companies are required to provide and complete SNI standards for the application of K3 which is expected to increase construction project worker performance. However, the reality found on the ground is where the company has several procedures which are operational standards that must be applied but are not fully implemented The occurrence of violations such as workers not wearing helmets or safety harnesses when working at heights. In this study using quantitative research methods. The population in this study are the parties involved in the construction of the rectorate and dean building of Mahasaraswati University Denpasar. The sampling technique used is porpusive sampling technique with a total sample of 45 respondents. This research uses descriptive hypothesis analysis. The test uses multiple correlation analysis and multiple linear regression. to determine the factors that influence the application of K3. The results of the hypothesis testing show that the application of K3 in the construction project of the Rectorate and Dean building of Mahasaraswati Denpasar University is classified as not being carried out properly. with the t-statistic value of the implementation factor of 0.129 <2.020, the supervisory factor of -0.070 < 2.020, the Management Factor -0.119 <2.020 and the variables of the implementation factor, the supervisory factor and the management factor only have an effect of 0.01% on the implementation of occupational safety and health ( K3)